Collective Bargaining and Management Rights - Chartier, Roger (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1960)
Summary In the last analysis, the firmest and deepest foundation of management rights is the need for an efficient coordination of multifarious activities and often divergent interests, with an aim to achieving the basic purpose of the business concern. Efficiency, however, is essentially a value whose définitions are all the more numerous and varied as science, in its present applications to industry, cannot lay claim to absolute certainty and accuracy. And even if it could, this would not alter in any way the political nature of decision-making. Such considerations lead to a re-examination of the notions of collective bargaining and joint management, as well as they induce new thinking on the specific function of management, which reaches beyond decision-making into the realm of coordination of means, activities, interests, and bargains.